Butterflies of Ambazari Garden and Surroundings of Nagpur City, Maharashtra, India - Tiple, Ashish D.; Khurad, Arun M. (Indian Forester, 2010)
A study was conducted to record the diversity of butterflies, its status and occurrence in the Ambazari garden and bare ground at lake side within Nagpur city, Central India, from June 2006 to May 2009. A total of 104 species of butterflies belonging to Papilionidae (07 species), Pieridae (13 species), Nymphalidae (33 species), Lycaenidae (37 species) and Hesperiidae (14 species) with 35 new records to Nagpur city were recorded. Most species were observed from the monsoon (hot/wet season) to early winter (cool/wet season) but thereafter butterfly population was declined in early summer (March). Among the butterflies recorded, 15 species come under the protection category as per the Indian Wild Life Protection Act 1972. The observations support the high value of this city garden and bare ground for conservation of butterflies and research on their biology.